2009
DOI: 10.1123/jsm.23.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Using Optimal Distinctiveness Theory to Understand Identification with a Nonlocal Professional Hockey Team

Abstract: In an attempt to understand the lived experiences of those individuals who grew up within the fan region of one professional hockey team yet chose instead to identify with a nonlocal alternative, the authors interviewed 20 Ontario (Canada) based fans of distant National Hockey League teams. Utilizing Brewer’s (1991, 2003) theory of optimal distinctiveness to examine the stories of participants, it was found that these fans maintained their team allegiances over time because doing so allowed them to achieve fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…This supports the work of Andrijiw and Hyatt (2009) who found that non-local hockey fans placed importance on distancing themselves from accusations of fair-weather fandom. Steven explained [ 4 1 _ T D $ D I F F ] that he felt sustaining identification during unsuccessful times would allow him to feel like he earned the right to extract a sense of vicarious achievement from the team's future successes.…”
Section: Framing the Futuresupporting
confidence: 88%
See 4 more Smart Citations
“…This supports the work of Andrijiw and Hyatt (2009) who found that non-local hockey fans placed importance on distancing themselves from accusations of fair-weather fandom. Steven explained [ 4 1 _ T D $ D I F F ] that he felt sustaining identification during unsuccessful times would allow him to feel like he earned the right to extract a sense of vicarious achievement from the team's future successes.…”
Section: Framing the Futuresupporting
confidence: 88%
“…These processes provided a basis for distinctiveness from other consumers and preferential [ 3 8 _ T D $ D I F F ] positioning within the in-group (e.g., Branscombe, Wann, Noel, & Coleman, 1993;Holt, 1995;. These sentiments extend previous work showing how identification with a team from the very beginning provides individuals with an identity unique from fans of other teams (Andrijiw & Hyatt, 2009). Our findings extend such work and illustrate how fans can differentiate themselves from others in the in-group who have not supported the team from the start.…”
Section: Owning Our Identitymentioning
confidence: 52%
See 3 more Smart Citations